Addition of Trichocladium canadense to an anaerobic membrane bioreactor: evaluation of the microbial composition and reactor performance - Fakhri, Hadi; Arabaci, Duygu Nur; Unlu, Ilayda Dilara; Yangin-Gomec, Cigdem; Ovez, Suleyman; Aydin, Sevcan (TAYLOR & FRANCIS LTD, 2021)
Membrane bioreactors are powerful systems for wastewater treatment and the removal of toxic compounds. However, membrane biofouling stands in the way of their widespread usage. In this study, the saprophytic fungus Trichocladium canadense was used as the bioaugmentor in an anaerobic membrane bioreactor (AnMBR) and its impact on membrane biofouling, biogas production, the microbial communities of the reactor and removal of the common antibiotics erythromycin (ERY), sulfamethoxazole (SMX) and tetracycline (TET) from synthetic wastewater was investigated. The results indicated that through bioaugmentation with 20% T. canadense, membrane biofouling was slowed by 25%, the chemical oxygen demand removal increased by 16% and a higher efficiency removal of ERY and SMX was achieved. The presence of T. canadense significantly increased the abundance and diversity of the biofilm archaeal community and the bacterial phylum Firmicutes, a known bio-foulant.
Keywords: Bioaugmentation; anaerobic membrane; bioreactor; biofouling; archaeal biofilms; antibiotics; next generation sequencing; ANTIBIOTIC-RESISTANCE GENES; WATER TREATMENT PLANTS; MUNICIPAL WASTE-WATER; REMOVAL; SEWAGE; BACTERIAL; ULTRAFILTRATION; METABOLITES; SEQUENCES; Biotechnology & Applied Microbiology; Marine & Freshwater Biology